Extraction of tannin and antioxidant activities from Musa acuminata cv. Cavendish peel by using various solvent - Ishak, Nur Arnisah; Baharuddin, Azhari Samsu; Ab Razak, Nor Asma (http://www.msmbb.my/images/publication/volume_27/issue_2/Complete-APJMBB272-supplementary_20190618.pdf, 2019)
Introduction: Banana (Musa spp.) is consumed fruit and among the highest hectarage fruit crops in Malaysia based on Crop Statistic Report, Department of Agriculture Malaysia 2016. Cavendish cultivars is the most commercially important banana in worldwide and highly potential for industrial export due to their nutrient and shelf life. Rejected banana peel from industry processing which are not equivalent to the standard are cheap and unlimited beneficial content. The usage of synthetic antioxidant contains harmful ingredient and effect human health in long period consumption. Thus, it is important to find an alternative ingredient such as tannin compound to replace it. Materials and method: This study investigates the different solvent: aqueous, methanol, ethanol, acetone and mixture of solvent with water for extraction to evaluate tannin, phenolic, flavonoid and antioxidant activity from unripe and ripe Cavendish banana peel. Result: Aqueous extract in unripe peel had the highest tannin content (172.30 mg TAE/g sample) compared to the ripe peel (135.090 mg TAE/g sample). Meanwhile, the total content of phenolic (209.154 mg GAE/g sample) and flavonoid (44.111 mg RE/g sample) were higher compare to other solvents. In addition, the antioxidant potential by DPPH and ABTS assay are comparable to other solvents. Discussion: Unripe peel of Cavendish banana contain high tannin and phenolic compound than ripe peel from aqueous extract. Aqueous extraction by using water is compromise approach that are eco-friendly nature, effective, cheap, safe and avoiding the toxic solvent. Conclusion: High antioxidant compound and activity could be obtained from unripe banana peel by using aqueous extraction.